Trade costs in international trade - Ali, Salamat (2018)
This thesis explores the effects of trade costs on international trade at macro and micro levels. It focuses on traditional and non-traditional sources of trade costs that imped trade flows at various phases of a typical export shipment: behind the borders, at the borders and beyond the borders. It initially examines the connection between trade costs and the composition of developing countries’ exports and then explores the responses of firms to additional costs associated with the security of supply chain imposed on Pakistan’s firms in the wake of events of 9/11. Following this, it investigates the differential effects of domestic and international transportation distance on the reactions of firm-level trade flows and multiple margins of trade. Finally, it considers the effects of exchange rate movement on agricultural exports. The thesis primarily uses micro-level information from administrative datasets of exports and intra-country trade (VAT dataset) from Pakistan. It also benefits from international data sources, such as the WB-UNESCAP trade costs dataset, WITS, WTO tariff profiles and the World Development Indicators (WDI). This thesis comprises four core chapters (2 to 5), excluding the introduction and conclusion. The analysis at a macro level (Chapter 2) finds the trade costs negatively affect the composition of developing countries exports in that the industries located in higher trade cost countries gain a relative smaller share of manufactured exports in the country’s overall exports. The effect is relatively greater for high trade cost sensitive industries (such as automobiles, electronics) and for high trade cost regions, especially Sub-Saharan Africa. The evaluation of trade effect of US security policy on Pakistan’s exports (Chapter 3) shows that following the implementation of Integrated Cargo Containers Control (IC3) programme, Pakistan’s exports to the US relative to the EU dropped by 15%, on average. Pakistan’s firms that were forced to switch from various export-processing stations to the one specific sea port equipped with the intrusive scanning and live monitoring technologies of the export cargos, experienced the largest decline. The subsequent policy interventions aimed at facilitating the process moderated this effect to some extent. The examination of differential effects of domestic and international distances on trade flows (Chapter 4) reveals that the marginal effect of inland distance to sea ports is much larger than that of international distance from sea ports to export markets. Moreover, both distances have heterogeneous effects along trade margins. Domestic distance impedes exports primarily through extensive margins (EM) of firms and product, whereas international distance restricts these mainly through quantity margins, in addition to constricting the EM. Although the trade-impeding effects of both components of distance have reduced over time, the drop has been relatively greater for the international leg. Finally, the investigation of response of agricultural exports to the exchange rate movement (Chapter 5) indicates that the domestic currency depreciation positively affects both intensive and extensive margins (IM and EM). The increase in the IM operates mainly through the channel of prices (75%), whereas the response of quantities is relatively smaller (25%). Similarly, the increase in extensive margins operates through widening of export basket and expansion of firms’ client base within existing markets. These responses however vary widely across products, markets, firms’ exporting experience, exchange rate regimes type and invoicing currency use. Four key policy implications emerge from the thesis. First, reducing trade costs could increase manufacturing exports from high trade cost regions, and the response would be larger in high trade cost sensitive industries. Second, improving access to trade-processing infrastructure could incentivise entry of more firms into exporting and encourage widening of export basket. Third, the unintended effects of response to potential threats to supply chain could offset the trade facilitating aspect of these scanning technologies and further restrict trade flows across national borders. Finally, the policy makers need to be cautious in using domestic currency depreciation as a policy tool to promote the growth of agricultural exports as the trade response might not be commensurate with the level of depreciation.